Online optical tomography system for detecting and measuring the diameters of solid and transparent objects - Jamaludin, J. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents an application of a charge coupled device (CCD) linear sensor and laser diode in an optical tomography (OPT) system. OPT is a non-invasive and non-intrusive tomography system consisting of an emitter with detectors. This paper is conducted in order to analyze and prove the capability of a laser with a CCD in an OPT system for detecting and measuring the diameter of an object that exists in crystal clear water. Experiments in detecting and capturing static solid and transparent objects are conducted using this hardware and software development. Statistical engineering methods were applied to analyze and validate the experimental data. Investigations of the effect of number of sensor views and object opacity level were also carried out in this paper. In conclusion, this paper has successfully developed an OPT system that is capable of detecting the appearance and measuring the diameter of objects with different opacity levels in non-flowing crystal clear water.